2020
DOI: 10.1080/08941920.2020.1833122
|View full text |Cite|
|
Sign up to set email alerts
|

Exploring Environmental Attitudes and Forest Program Uptake with Nonindustrial Private Forest Owners in Michigan

Abstract: The study focuses on forest management in four Michigan counties (Alpena, Barry, Newaygo, and Washtenaw). The study examines: 1) management practices on private land, and 2) how incentive programs can encourage landholders to develop a forest stewardship plan, a custom plan that describes your personal goals, unique forest resources, and suggested management activities for your land. This study will inform state and national programs that address landholders' needs. Description of ParticipationAs the owner of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Several studies have explored nonindustrial private forest (NIPF) landowners' attitudes towards and perceptions of forest certification programs in an effort to promote future enrollment in the United States. For example, research has found a range of support for private forestland certification [4][5][6], as well as a multitude of drivers for certification program participation, including passion for environmental stewardship [7], education [4], age, and management activity level [8]. Furthermore, research investigating barriers to certification for NIPF landowners has consistently found that certification costs [3,5,[9][10][11][12] and strict program requirements (e.g., required management plans) [9][10][11] are significant hurdles for landowners.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have explored nonindustrial private forest (NIPF) landowners' attitudes towards and perceptions of forest certification programs in an effort to promote future enrollment in the United States. For example, research has found a range of support for private forestland certification [4][5][6], as well as a multitude of drivers for certification program participation, including passion for environmental stewardship [7], education [4], age, and management activity level [8]. Furthermore, research investigating barriers to certification for NIPF landowners has consistently found that certification costs [3,5,[9][10][11][12] and strict program requirements (e.g., required management plans) [9][10][11] are significant hurdles for landowners.…”
Section: Introductionmentioning
confidence: 99%